Peran Dinas Pariwisata Pemuda dan Olahraga dalam Mendorong Pertumbuhan Ekonomi Kreatif pada Sentra Kuliner Malam Painan Night Culinary Kabupaten Pesisir Selatan - Afni, Nurul; Jumiati, Jumiati (PUBLICNESS: Journal of Public Administration Studies, 2025)
The government has an essential role in encouraging the growth of the creative economy through various policies and support. The Youth and Sports Tourism Office (Disparpora) of Pesisir Selatan Regency is committed to developing culinary creative economy businesses and tourist villages. This study aims to analyze the implementation of the Youth and Sports Tourism Office's role in encouraging the Creative Economy's growth in the Painan Night Culinery Center of Pesisir Selatan Regency. This qualitative study uses a descriptive approach and literature angle as well as interview, observation, and documentation studies. The results of this study show that the Tourism, Youth and Sports Office of Pesisir Selatan Regency has implemented various programs. This implementation includes three leading roles of the government, namely as a facilitator in providing business locations and access to capital, as a catalyst through fostering traders and tourism promotion, and as a regulator in managing cleanliness and order in the area.